Game-theory based trading analysis between distribution network operator and multi-microgrids. (February 2019) - Lin, Wei; Jin, Xiaolong; Mu, Yunfei; Jia, Hongjie; Yu, Xiaodan; Pu, Tianjiao; Chen, Naishi
Abstract: A game-theory based trading analysis between distribution network operator (DNO) and multi-microgrids (multi-MGs) is proposed in this paper. Firstly, the model of DNO and MG are developed respectively. The operational objective of the DNO is trading profit ( TP ) maximization and the operational objective of the MGs are operation cost ( OC ) minimization. Secondly, a game composed of DNO and MGs is formulated and the Karush–Kuhn–Tucker (KKT) method is utilized to achieve the Nash Equilibrium (NE) point. Numerical results show that the proposed solution method is able to balance different interest of DNO and MGs simultaneously and the trading behaviors under different market prices are analyzed, which contributes to the optimal operation in aspect of payoff maximization.